Basic aeroelastic stability studies of hingeless rotor blades in hover using geometrically exact beam and finite-state inflow - Amoozgar, M.; Croce, A.; Riboldi, C.E.D.; Trainelli, L. (My University, 2017)
An approach to aeroelastic stability analysis of hingeless rotor blades in hover is presented which combines a geometrically exact beam theory and a three-dimensional finite-state dynamic inflow theory, using the Cp- Lambda finite-element multibody code. The aeroelastic system is solved by an efficient numerical integration scheme, and the lead-lag damping is determined from the time response results. The method is validated by application to a two-bladed hingeless rotor without precone, and a remarkable agreement with reference results is observed, in dependence of the number of finite inflow states. Then, results are obtained with positive and negative precone angles, showing the effect of these variations on lead-lag stability.